2020
DOI: 10.5897/jaerd2018.0946
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between public and private extension services for sugarcane production in Muzaffargarh District, Punjab, Pakistan

Abstract: Sugarcane industry is at second position after textile industry in Pakistan. By the export of refined sugar, it plays a significant role in the economy of the country. Public and private sectors extension field staff work with sugarcane growers to improve their per acre yield. The research was conducted to compare and identify the services provided by those two sectors. A total of 150 respondents were selected randomly and interviewed to collect data through a structured interview schedule. The data were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…They further emphasised that PPPs in agricultural extension are increasingly recognised as an effective mechanism for enhancing public service provision and implementing development programs. In their comparison of private and public extension services, Farooq et al (2020) observed that both sectors employed similar extension teaching methods for information dissemination. However, the private sector outperformed the public sector in terms of providing commodities, offering technical assistance, and advocating for farmers.…”
Section: Introductionmentioning
confidence: 99%
“…They further emphasised that PPPs in agricultural extension are increasingly recognised as an effective mechanism for enhancing public service provision and implementing development programs. In their comparison of private and public extension services, Farooq et al (2020) observed that both sectors employed similar extension teaching methods for information dissemination. However, the private sector outperformed the public sector in terms of providing commodities, offering technical assistance, and advocating for farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture is one of the key sources of poverty alleviation in developing countries (Agbarevo, 2013) especially in Pakistan (Azam and Shafique, 2017;Anwer et al, 2015). This sector not only fulfils the food requirements of the country but also creates the employment opportunities for majority of the peoples (Mengal et al, 2017;Muhammad et al, 2020). Farmers are the key pillars of the agriculture system.…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, somehow the literature is scanty on the topic. Few studies such as (Davidson and Ahmad, 2002;Mengal et al, 2018;Talib et al, 2018;Muhammad et al, 2020) had investigated the working of extension advisory services in the Pakistan. Most of them were of local nature or specific for the one crop and weak in its implications for the development of public and private sector extension service.…”
Section: Introductionmentioning
confidence: 99%
“…The ''economic'' values may reflect the market situation, preferences (Magnussen 1990). Numerous investigations was carried out on selection indices in plant breeding like Lal and Singh (1997) on melon, Gomaa et al, (1999) on cotton, Daliya and Wilson, (2004) on eggplant, Rabie et al, (2004) on rice grain, Hussein et al, (2008) on rice, Muhammad and syed, (2010) on sweet corn, Mohammad et al, (2014) on sugarcane, Nyo et al, (2020) on rice grain and Gomes et al, (2021) on melon. The authors reported that there was more success using selection index for increasing expected response to selection than direct selection of different traits at the same time.…”
mentioning
confidence: 99%